Numerical Study on Tidal Mixing in the Bohai Sea. Issue 1 (2nd January 2019) - Zhao, Yifei; Deng, Zengan; Yu, Ting; Wang, Hu
Abstract: The spatial and temporal variability of tidal mixing in Bohai Sea is studied using a numerical approach. In calculating tidal mixing, accurate barotropic tidal current is obtained via a harmonic analysis package utilizing the simulated current output from a high-resolution regional ocean model. And a "small-scale" roughness map is adopted to describe the detailed topographic features of Bohai Sea. It is shown that the tidal mixing estimated in Bohai Sea is much higher than the level of global background, and fluctuates considerably at some regions within a single day. In Liaodong Bay, Bohai Bay and Bohai Strait, the mixing varies greatly, with the peak value of O (10 −2 ) m 2 s −1 . The order of magnitude of mixing in Laizhou Bay is about O (10 −5 ∼10 −3 ) m 2 s −1 . Mixing with background level of O (10 −5 ) m 2 s −1 only appears in central area. Result also shows that rough topography plays relatively a more important role than tidal current in enhancing diapycnal mixing in Bohai Sea. The distributions of tidal mixing in selected sections reveal that the vertical stratification in Bohai Sea is not obvious, generally renders a barotropic structure.